IMPLEMENTATION OF TAHFIZH AND TAFAQQUH FIDDIEN ASSIGNMENTS AT SMPIQU ALBAHJAH AZZAINIYAH BATAM - Maulana, Syafiq; Mujahidin, Endin; Handrianto, Budi (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
SMPIQU Albahjah Azzainiyah Batam School has one of the leading programs as a local content by implementing the Tahfidz and Tafakkuh Programs Each class must be able to participate in tahfidz and Tafakkuh activities held and assigned by the school. This observation aims to: (1) Know the implementation of tahfizh and Tafakkuh programs and (2) as a step for planning that can be carried out properly to achieve maximum results in the future. Where the development of students in the Albahjah Azzainiyah hut aims to instill the values of piety, independence, discipline, responsibility, simplicity, and skills to realize the vision, mission, goals, and targets of the school. The implementation of the assignment of Tahfidz and Tafaqquh fiddien is an observation of teacher activities to improve their role in education, especially character education at SMPIQU Azzainiyah Batam. The analysis used is observation and field participation. The subject of this study was a supervisor and teacher at SMPIQU AAlbahjah Azzainiyah Batam. While the object of this study is the Implementation of Tahfidz and Tafakuh Fiddin Assignments at SMPIQU Albahjah Azzainiyah Batam. Data observation is carried out by selecting the data obtained and then collected for analysis and conclusions. This research uses a qualitative approach, with a case study approach at SMPIQU Azzainiyah Batam. Data was obtained in this study through observation, interviews, and documentation studies. Based on the data obtained, researchers use descriptive analysis, namely by describing or describing what are the findings in the field related to the implementation of the Qur'an tahfidz and tafakkuh programs at SMPIQU Azzainiyah Batam